The relationship between athletes’ belief in nutritional supplements and disengagement of sports ethics with doping - Guvendi, Burcu; Yagmur, Rifat (Progress in Nutrition, 2020)
Study Objective: The aim of this study was to examine the relationship between the belief of athletes in nutritional supplements and the disengagement from sports ethics with doping. Methods: A total of 627 athletes with mean age of 22.76±5.30 years, mean of 9.51±5.64 sports years, 307 of whom were women, and 320 of whom were men, participated in the study. The research used the scale of belief in nutritional supplements and the disengagement from sports ethics with doping scale. The Mann Whitney U and Kruskal Wallis tests were used to analyze data from non-parametric tests. Results: The results had shown that athletes were moderate agreed with the belief in sports nutritional supplements, while they didn’t agree with the disengagement from sports ethics with doping. According to the correlation analysis, there was a positive low level of significant correlation between the total score for the sports nutritional supplements belief scale and the total score for the disengagement from sports ethics with doping. A significant difference was found in the total score of sports supplements based on gender, nationality, and age variables, and in the total score of the disengagement from sports ethics with doping according to national and branch variables. Conclusion: As a result, increased belief in nutritional supplementation in sport appears to have led athletes to disengage from sport ethics with doping.